Door-to-Balloon and Door-to-Needle Time for ST-Segment Elevation Myocardial Infarction in the U.S - Vasaiwala, Samip; Vidovich, Mladen I. (Journal of the American College of Cardiology, 2009)
(1) from Denmark recommended that the committee responsible for further updates to the American College of Cardiology/American Heart Association (ACC/AHA) guidelines for ST-segment elevation myocardial infarction (STEMI) and the D2B (Door-to-Balloon) Alliance shift focus toward initiates that would reduce system delay in primary percutaneous coronary intervention (PCI) patients.